Gender and Climate Change Workshop in Nairobi, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 14 May 2014 the World Agroforestry Centre held a workshop on new findings related to gender and climate change. The workshop was organised by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and International Food Policy Research Institute (IFPRI).